ERP Systems for Effective Management - James Prem Kumar, P. (Prabandhan: Indian Journal of Management, 2009)
Over the past few years, integrated enterprise resource planning (ERP) applications have brought a new way of delivering operation information. The advantages of these changes have transformed many organizations, which improved financial visibility, streamlined supply chain processes, and minimized human resource (HR) processes and overhead.